Micro finance - Rehman, Waheed (2008)
This research provides an overview of micro finance industry in Pakistan. Micro Finance in Pakistan is at its initial stage. The organized micro finance activities started in 2001 as a result of Micro Finance ordinance 2001. The establishment of first micro finance bank of Pakistan is the result of this ordinance. The poverty level in Pakistan is about 33% to 35%. It means one third of the population of 150 Millions people of Pakistan is below the poverty line. The women are much more vulnerable then men. The gap between the rich and poor increases day by day. It will further adverse the situation in the society. Micro finance is the tool that can bring the positive change in the life of the poor people of Pakistan. The government of Pakistan and some other organization like Khushhali bank, Kashf foundation, Micro Finance Bank of Pakistan, etc. doing there efforts to increase there out reach but there are a large numbers of challenges in the way that barrier the out reach as a whole and particularly for women.